2021
DOI: 10.3390/pharmaceutics13040579
|View full text |Cite
|
Sign up to set email alerts
|

Design and Evaluation of Dissolving Microneedles for Enhanced Dermal Delivery of Propranolol Hydrochloride

Abstract: Oral propranolol hydrochloride has been the first-line treatment for infantile hemangioma (IH), whereas systemic exposure to propranolol has the potential of causing serious adverse reactions. Dermal delivery of propranolol is preferable due to high local drug concentration and fewer adverse effects. However, propranolol hydrochloride (BCS class I) is highly hydrophilic and has difficulty in penetrating the stratum corneum (SC) barrier. Dissolving microneedles (MNs) are an efficient tool for overcoming the bar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 75 publications
(29 reference statements)
0
31
0
Order By: Relevance
“…In this study, an aqueous blend of PVA and PVP was used in the DMN formulation with various concentrations, as shown in Table . Previous studies have shown that the combination of these two polymers results in better mechanical strength and penetration ability than when used singly. , PVP is a polymer with good hardness, but when used alone, it will provide inadequate mechanical strength for DMN due to its hygroscopicity. , The addition of PVA will fix the shortcomings of PVP. The combination of PVA and PVP causes the formation of hydrogen bonds between the CO group of PVP and the −OH group of PVA to provide adequate mechanical strength .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, an aqueous blend of PVA and PVP was used in the DMN formulation with various concentrations, as shown in Table . Previous studies have shown that the combination of these two polymers results in better mechanical strength and penetration ability than when used singly. , PVP is a polymer with good hardness, but when used alone, it will provide inadequate mechanical strength for DMN due to its hygroscopicity. , The addition of PVA will fix the shortcomings of PVP. The combination of PVA and PVP causes the formation of hydrogen bonds between the CO group of PVP and the −OH group of PVA to provide adequate mechanical strength .…”
Section: Resultsmentioning
confidence: 99%
“…When applied, DMN will form small pores as channels for the drug or drug MPs to pass through . DMN-loaded drugs can deliver drugs directly; meanwhile, for drug MPs, it is necessary to pass through the polymer matrix first after being released from DMN . This causes the MPs in the DMN to permeate less than the pure drug in the same time duration and provides longer MTF availability.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent study, He et al . fabricated DMNs by a two-step casting procedure that used HA and PVP as matrix materials for loading propranolol hydrochloride in needle tips ( Figure 10 ) 158 . The MNs had outstanding mechanical strength to penetrate SC, as well as superior dissolution ability to release propranolol hydrochloride.…”
Section: The Applications Of Nanocarrier- or Mn-based Transdermal Del...mentioning
confidence: 99%
“…(C) Fluorescence microscopy images of the MNs with fluorescein isothiocyanate isomer (FITC) as a tracer reagent. Adapted with permission from reference 158 . Copyright 2021 Multidisciplinary Digital Publishing Institute.…”
Section: Figurementioning
confidence: 99%
“…Oral NSAIDs, such as ibuprofen sustained-release tablets and ibuprofen sustained-release capsules, are nonselective cyclooxygenase (COX) enzyme inhibitors, which can simultaneously inhibit COX-1 and COX-2 (Thakur et al., 2018 ). However, the inhibition of COX-1 could cause gastrointestinal discomfort (Solomon et al., 2017 ). The selective COX-2 inhibitor Celecoxib has low solubility (3–7 μg/ml), strong first-pass metabolism and rapid plasma clearance rate, so Celecoxib capsules have only 22–40% bioavailability when administered orally (Quinones & Pierre, 2019 ).…”
Section: Drug Dosage Form For Treating Ramentioning
confidence: 99%